Eigenvalue Distribution of Bipartite Large Weighted Random Graphs. Resolvent Approach - Vengerovsky, V. (Журнал математической физики, анализа, геометрии, 2016)
We study an eigenvalue distribution of the adjacency matrix A(N,p,α) of the weighted random bipartite graphs Исследуется распределение собственных значений матрицы смежности случайного двудольного графа.